Personal Letters Between Lu Qingsheng and Jiang Zhenyuan, 1961-1986. - Zhang, Letian (Chronicles of Contemporary Chinese Social Life Ser., 2018)
This rare unusual collection contains a total of 774 letters, most of which were written by a couple, Mr. Lu and Ms. Jiang, who lived apart for more than fifteen years between 1961 and 1986 and relied mainly on letter-writing to communicate. They passionately revealed romantic love and conjugal compassion to each other; they discussed mundane details of everyday family life including management of the household economy, efforts of interacting with in-laws, relatives, and friends, learning course of raising children, and strategies of coping with financial hardship. They also sincerely engaged each other in a soul-searching process of making themselves into socialist subjects and participating in various political campaigns. The content of these letters is as rich and complicated as the flow of life itself in which the personal, economic and political are intermingled together. The degree of sincerity and honesty in these letters is greater than that in many other kinds of historical data because the authors are not writing for public consumption. This rare collection of personal letters presents not only a huge amount of original and disaggregated data but also constitutes an oral history of social life in China that is unintentionally being recorded by the authors.